2013
DOI: 10.1371/journal.pone.0056744
|View full text |Cite
|
Sign up to set email alerts
|

Air-Stimulated ATP Release from Keratinocytes Occurs through Connexin Hemichannels

Abstract: Cutaneous ATP release plays an important role in both epidermal stratification and chronic pain, but little is known about ATP release mechanisms in keratinocytes that comprise the epidermis. In this study, we analyzed ATP release from cultured human neonatal keratinocytes briefly exposed to air, a process previously demonstrated to trigger ATP release from these cells. We show that exposing keratinocytes to air by removing media for 15 seconds causes a robust, long-lasting ATP release. This air-stimulated ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 63 publications
1
58
0
Order By: Relevance
“…Keratinocytes for example may release ATP via connexin hemichannels (Barr et al, 2013), and heat activation of TRPV3 in keratinocytes was proposed to transmit information via ATP release (Mandadi et al, 2009), a notion consistent with reduced non-noxious warmth sensitivity of P2X3 −/− mice (Souslova et al, 2000). ATP can also be released from damaged cells in a non-specific manner, and P2X3 −/− mice showed reduced responses to formalin-induced pain.…”
Section: Ligand Activated and Chemosensitive Ion Channelsmentioning
confidence: 92%
“…Keratinocytes for example may release ATP via connexin hemichannels (Barr et al, 2013), and heat activation of TRPV3 in keratinocytes was proposed to transmit information via ATP release (Mandadi et al, 2009), a notion consistent with reduced non-noxious warmth sensitivity of P2X3 −/− mice (Souslova et al, 2000). ATP can also be released from damaged cells in a non-specific manner, and P2X3 −/− mice showed reduced responses to formalin-induced pain.…”
Section: Ligand Activated and Chemosensitive Ion Channelsmentioning
confidence: 92%
“…These results indicated that the stretch-induced mechanosensitive ATP release occurs through hemichannels. Recent studies have demonstrated pharmacologically that when keratinocytes are exposed to air, it results in ATP release through connexin hemichannels (Barr et al, 2013), and when keratinocytes, including HaCaTs, are exposed to hapten, it results in ATP release through pannexin 1 (Onami et al, 2014).…”
Section: Fig 7 the Inhibitory Effects Of Various Inhibitors Of Atp-camentioning
confidence: 99%
“…ET A receptor-expressing nociceptive neurites terminate in the epidermis where they are surrounded by keratinocytes. Keratinocytes release a variety of pro-algesic molecules that activate excitatory receptors on nociceptive nerve endings, including glutamate, CGRP and ATP [2; 11; 15; 20; 33]. In particular, cutaneous ATP release has been implicated in numerous types of acute and chronic pain [5; 9].…”
Section: Introductionmentioning
confidence: 99%